Therapeutic plants found in agrocenoses of the middle Vistula River Valley mesoregion. - Ługowska, Maria; Skrzyczyńska, Janina; Skrajna, Teresa (Plant Breeding and Seed Science, 2010)
Studies on the segetal flora of the Middle Vistula River Valley mesoregion were carried out between 2003 and 2006 in cereal and potato crops and in stubble fields (117 localities). A total of 184 medicinal vascular plant species were noted in the studied agrocenoses. Native plants (68%) dominated over species brought to Poland (32%). Hemicryptophytes (83 spp.), therophytes (74 spp.) and geophytes (26 spp.) were the most numerous groups of life forms. Perennials (55%) prevailed over short-lived plants (45%). Very rare and rare species (61%) built up the most numerous group of species. Their populations usually consisted of single specimens. Only a_few of the medicinal plant species occured as larger populations. They were Aphanes arvensis, Stellaria media and Galium aparine in cereals, Equisetum arvense, Stellaria media, Chenopodium album, Elymus repens, Plantago major, Polygonum amphibium, Mentha arvensis, Plantago intermedia, Polygonum hydropiper and Gypsophila muralis in stubble fields, as well as Stellaria media in potato cultivations...